Masyarakat Sipil dalam Pemilihan Umum 2024 di Kecamatan Banyuwangi Kabupaten Banyuwangi: Studi di Dapil 1 pada Pemilihan Calon Legislatif - Ratna Ani Lestari; Mangihut Siregar; Ismail A. Rahim; Moh. Ali Shulthoni (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
Indonesia has just held a general election, precisely on February 14, 2024. The public is faced with the election of candidates for President/Vice President, DPR RI, DPD RI, Provincial DPR, Regency/City DPR, in accordance with the Election Law, backed by the Constitutional Court Decision Number 14/PUU-XI/2013. This study uses the theory of political participation by A. Rahman H.I (2007). This study is a qualitative study, with data collection from interviews and documentation, data analysis using Miles & Huberman (2014). The results of this study indicate that participation in electoral district 1 can be said to be active participation, this is because the candidates have their own way to attract the sympathy of the public in electoral district 1.